Anticorruption Measures in the Healthcare System During the Pandemic - А. А. Satybaldin; E. G. Vanhemping; R. M. Ruzanov; T. M. Zharlygassinov (Экономика: стратегия и практика)
This article aims to analyze anti-corruption measures in the healthcare system during a pandemic. During this study, the problem of corruption was studied as a subject of interdisciplinary analytical discourse in the global and domestic expert space. Also, based on the results of the content analysis of critical analytical documents from leading international anti-corruption organizations, specific health problems during the pandemic, typical for all countries of the world, were identified. As a result of the analysis of international documents, Kazakhstani scientific and analytical articles, leading state initiatives of Kazakhstan in the field of reforming the country, key conclusions were drawn regarding the understanding of strategic ways of sustainable development through the introduction of an effective and efficient mechanism for adapting world standards to the Kazakhstani field of combating corruption in general and to the system public administration in the healthcare system in particular. The study was carried out based on a comparative analysis of expert assessments of corruption in the healthcare sector. To determine the adaptive effectiveness of applying the recommendations of the global anti-corruption expertise in Kazakhstani practices of combating corruption in the public health administration system, an empirical study of institutional aspects in anti-corruption international analytics was undertaken. This made it possible to see the significance of local features and systemic prerequisites that determine the success of anti-corruption actions in Kazakhstan. During the preparation of the article, the following sources were used: socio-economic expertise of Interpol; National Report on Combating Corruption; analytics from a global anti-corruption NGO.